2012
DOI: 10.1007/s11604-012-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic arterial embolization for unresectable hepatocellular carcinomas: do technical factors affect prognosis?

Abstract: Selective embolization contributes to survival in patients with HCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…Conventional transarterial chemoembolization techniques also have an impact on patient survival. In patients with HCC r 7 cm and five or fewer lesions, the prognosis of patients who underwent selective/superselective conventional transarterial chemoembolization was significantly more favorable than the prognosis of patients who underwent nonselective (lobar) conventional transarterial chemoembolization (P = .033) (44). These studies suggest that superselective conventional transarterial chemoembolization is indicated for patients with Child-Pugh scores of 5-8 and HCC r 7 cm and five or fewer lesions.…”
Section: Indication For Superselective Conventional Transarterial Chementioning
confidence: 81%
“…Conventional transarterial chemoembolization techniques also have an impact on patient survival. In patients with HCC r 7 cm and five or fewer lesions, the prognosis of patients who underwent selective/superselective conventional transarterial chemoembolization was significantly more favorable than the prognosis of patients who underwent nonselective (lobar) conventional transarterial chemoembolization (P = .033) (44). These studies suggest that superselective conventional transarterial chemoembolization is indicated for patients with Child-Pugh scores of 5-8 and HCC r 7 cm and five or fewer lesions.…”
Section: Indication For Superselective Conventional Transarterial Chementioning
confidence: 81%
“…By contrast, in patients with substage B2 HCC, the liver function after the third and fifth TACE sessions deteriorated compared with that after the first TACE session. As the liver function is impaired by TACE, it is recommended to perform TACE as selectively as possible [11,37,38] . However, it is difficult to perform TACE selectively, especially for multiple HCCs, and TACE could also affect the normal liver and, consequently, impair the liver function.…”
Section: Discussionmentioning
confidence: 99%
“…On multivariate analysis, selective TACE, the AFP level at the time of the first TACE, and radiologic tumor response were useful prognostic factors for predicting OS. Therefore, it is conceivable that performing selective TACE, which is commonly applied in Japan, leads to prolonged OS in our cohort [32]. …”
Section: Discussionmentioning
confidence: 99%